Enabling Qualified Anonymity for Enhanced User Privacy in the Digital Era - Bolgouras, Vaios; Papadamou, Konstantinos; Stroinea, Ioana; Papadakis, Michail; Gugulea, George; Sirivianos, Michael; Xenakis, Christos (My University, 2023)
This paper presents a privacy-enhancing identity management platform designed to address the challenges associated with online identity verification and privacy protection. INCOGNITO offers a comprehensive solution by leveraging concepts such as Qualified Anonymity and cryptographic credentials, along with technologies including blockchain, Tor Network, and software stacks like Idemix. By employing these mechanisms, INCOGNITO aims to enable users to securely acquire and manage their identity attributes, while preserving their privacy and ensuring compliance with both regulatory bodies and Service Providers' requirements. The platform facilitates the issuance and verification of cryptographic credentials, granting users access to online services based on fine-grained subsets of their identity attributes. Furthermore, the effectiveness and feasibility of the platform are demonstrated through two pilot projects focused on online multimedia content sharing and identifying bots or fake users in online social networks. These pilots showcase the practical applicability of INCOGNITO in solving identity-related challenges while safeguarding user privacy and security.
Keywords: Artificial Intelligence; Cryptographic credentials; Identity Management; Privacy